Virtual reality public speaking training: effectiveness and user technology acceptance - Bachmann, Manuel; Subramaniam, Abimanju; Born, Jonas; Weibel, David (Frontiers in Virtual Reality, 2023)
Public speaking is a fundamental task in many professional or personal situations. At the same time, there is widespread fear of it, and it takes practice to present well. Previous studies suggest that Virtual Reality Public Speaking Training (VRPST) offers a promising opportunity for this. However, studies evaluating objective and subjective indicators are lacking so far, and valid control conditions are missing in previous studies. We aimed to overcome these drawbacks. In our experiment, participants (N = 42) had the task of presenting a card game to a four-person audience using five provided PowerPoint slides within a time limit of five minutes. They prepared either using VRPST or using common selfdirected preparation (control condition), being randomly assigned to a condition. Both groups were instructed to prepare for the task at home and given 30 minutes to learn the rules of the game and present them using the slides. The control group was given an additional 30 minutes to prepare individually for the presentation task at home. The experimental group received an additional 30-minute VRPST session. This training session was done without specific feedback and the presentation was repeated three times. The quality of the rule explanation, the audience-assessed presentation quality, and the subjects' self-assessed presentation quality were measured. Our results indicate that the VRPST is effective. Subjects who completed the VRPST did a better job of explaining the rules and were better rated by the audience. In addition, the experimental subjects also tended to rate their presentation better in the VRPST condition. Further analyses of those participants who completed the VRPST show high technology acceptance. Our results show the VR training had a significant performanceenhancing effect and that participants would use the VRPST if it were available to them. It seems that practicing a presentation in VR is useful and even better than a conventional preparation.